KEBAHASAAN SINEMATIK BERNUANSA PLURALITAS DALAM IKLAN BNI TAPLUS ANAK - Rustono Farady Marta; Patricia Robin (Communication, 2019)
Early education introduces children to how to manage money, especially since growing up to become a person who values money more. Related to this, PT. Bank Negara Indonesia, Tbk (BNI) released the BNI Taplus Anak program for children aged 0 to 17 years. To proclaim the service, advertisements were made that were very close to the reality of the lives of parents and children. This advertisement tells a group of bands with the name "Kancil" which consists of 5 people with high plurality nuances where they have different ethnicity, or skin color but live in harmony in order to realize the dream of becoming a band that follows the competition. The problem of this research lies in the meaning of the sign of the cinematic linguistic pattern of the BNI Taplus Anak version of the Kancil Band. This study aims to determine the mapping of storytelling patterns in the BNI ad, then identify the categorical of each of the cinematic lines and reveal the meaning of the sign. This study takes the qualitative study of Christian Metz's Cinema Semiology which seeks to build a model of the film linguistic system as text, which is found in sintagma as a structured group of signs. Research findings show that implicit meanings of plurality order are forward and have Systematic flow is not only based on the image of the product as a supporter of the value of its production, but moral responsibility in presenting story ideas is successfully presented to the audience. The filmmaker who creates the creative idea of making this advertisement succeeds in knitting the story in a congruent manner, the pattern of storytelling chronologically traced at a level where the scope of the framework is smaller implies a similar and consistent meaning in the form of plurality.